2016
DOI: 10.1155/2016/6757154
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones, Oxidative Stress, and Inflammation

Abstract: Inflammation and oxidative stress (OS) are closely related processes, as well exemplified in obesity and cardiovascular diseases. OS is also related to hormonal derangement in a reciprocal way. Among the various hormonal influences that operate on the antioxidant balance, thyroid hormones play particularly important roles, since both hyperthyroidism and hypothyroidism have been shown to be associated with OS in animals and humans. In this context, the nonthyroidal illness syndrome (NTIS) that typically manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
282
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(299 citation statements)
references
References 139 publications
(144 reference statements)
8
282
0
9
Order By: Relevance
“…These conflicting results suggest that the effects of TH on neutrophil ROS generation cannot be entirely explained by direct effects of TH on these cells. The link between TH metabolism and oxidative stress that occurs outside innate immune cells has been reviewed elsewhere and is beyond the scope of this review (Mancini et al 2016).…”
Section: Effects Of Thyroid Hormones On Neutrophil Functionmentioning
confidence: 99%
“…These conflicting results suggest that the effects of TH on neutrophil ROS generation cannot be entirely explained by direct effects of TH on these cells. The link between TH metabolism and oxidative stress that occurs outside innate immune cells has been reviewed elsewhere and is beyond the scope of this review (Mancini et al 2016).…”
Section: Effects Of Thyroid Hormones On Neutrophil Functionmentioning
confidence: 99%
“…4,5 The infection induces infiltration of polymorphonuclear that if nor cleared effectively, than replaced gradually by an immunologically-mediated, chronic, and latter induce pro-inflammatory cytokines production by local or systemic, 1,2-6 as aresult, gastric epthelium is not the only one target of H pylori pathologic manifestationbut also affected to some extradigestive conditions, including endocrine disorders, including autoimmune thyroid disorders (ATD) such as autoimmune atrophic thyroiditis and Hashimoto's thyroiditis, or thyroid mucosal associated lymphocyte tissue (MALT) lymphoma that has been epidemiologically proven,. 1,7,8 Even there have been controversial report about the link between H pylori infection and thyroid disorders, but some studies have been sucsesfully reported an increased prevalence of H pylori in people with ATD and relationship between H pylori infection and the presence of high titers of thyroid auto-antibodies, such as antithyroglobulin (anti-Tg) and anti-thyroperoxidase (anti-TPO) antibodies resulting in abnormalities of gastric secrtory fuction. 1 Other studies have been demonstrated that some bacteria and viruses are able to mimic the antigenic profile of the thyroid cell membrane, thereby playing an important role in the pathogenesis of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the thyroid may be the target by autontibodies after H pylori infection. 1,7,8 Chronic inflammation that caused by H pylori can induces oxidative stress that has been shown to be associated with both hyperthyroidism and hypothyroidism. 8,9 however the mechanisms of oxidative stress generated in to hypothyroidism is low availability of antioxidants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the key connection between the inflammatory and oxidative stress and the development of atherosclerosis is increased level of C-reactive protein (CRP) [8,11]. It was established that the increased activity of low-intensity inflammation, the most studied marker of which is CRP, is very important for the development of both inflammatory and non-inflammatory thyropathies of different genesis [4,7,9].…”
mentioning
confidence: 99%